Pengaruh Pengaruh Likuiditas Dan Leverage Terhadap Profitabilitas Pada PT. Gudang Garam Tbk (Tahun 2016 – 2020): Likuiditas, Leverage, Profitabilitas - Corrina Dian; Erika Dwi; Bella Khoirun; Yahya Wahyu; Dwi Ermayanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study hopes to check the resultant liquidity and leverage on profitability. The analytical method used is a quantitative regulation which is found to be additionally investigated by non-participation or indirectly, in particular by collecting, presenting and researching secondary evidence in the form of financial complaints of PT. Gudang Garam Tbk 2016 - 2020. The results of the uniformity check of the Kolmogorov-Smirnov checks that were carried out showed that the causes used in the analysis were based on a basic distribution plus a perception period of 0.079 (more designs sourced 0.05). In this unit, the profit of PT Gudang Garam Tbk in 2016 - 2020 is influenced by the constituents of liquidity and leverage.